Rapid Production of a Novel Al(III) Dependent Bioflocculant Isolated From Raoultella ornithinolytica 160-1 and Its Application Combined With Inorganic Salts - Ding, Rui; Luo, Laipeng; Han, Ruixiang; Zhang, Meiling; Li, Tingting; Tang, Jihui; Huang, Shenghai; Hong, Jiong (Frontiers in Microbiology, 2021)
An efficient bioflocculant-producing strain, Raoultella ornithinolytica 160-1, was identified by 16S rRNA and mass spectrometry analyses. Rapid production of bioflocculant EPS-160 was obtained with 10.01 g/(L·d) after optimized by response surface methodology. With the aid of Al(III), more than 90% flocculation activity of EPS-160 at 8 mg/L dosage was achieved in five minutes. Thus, this novel Al(III) dependent bioflocculant was used in combined with chemical coagulants AlCl3 to remove kaolin suspensions and wastewater treatment. The results indicated that the addition of EPS-160 in aggregation system not only largely improved the floccualtion ability than the individual use of chemical flocculant (over 30 percent), but also overcome the decrease of flocculation activity due to the overdose of AlCl3 and maintained the optimum dosage of AlCl3 in a wide range (11-23 mg/L). The zeta potentials and EPS-160 structure indicated that both charge neutralization and bridging were the flocculation mechanism with kaolin. During the wastewater treatment, this composite flocculants consisted of EPS-160 and AlCl3 also had great performance for turbidity elimination. Moreover, with the properties of high flocculation activity, hyperthermal stability, pH tolerance and nontoxicity, EPS-160 shows great potential applications.